Born at the Right Time: Examining the Effect of Relative Age on Mental Health in Adulthood - Petri Böckerman; Mika Haapanen; Jani Kuhakoski; Tiina Kuuppelomäki; Juuso Villanen (Institute of Labor Economics (IZA), 2024)
This paper examines the understudied effect of relative age on mental health in adulthood. Our empirical analysis utilizes nationwide Finnish register-based data on mental health, encompassing a spectrum of conditions from severe to less severe mental health problems. To identity causal effects, we employ a regression discontinuity design centered around the January 1 cutoff. We find that being born at the start of the year leads to better mental health outcomes. Notably, these effects, primarily influenced by relative school starting age, are driven by women in their late twenties.
Keywords: I10; I14; I31; J13; 330; relative age; mental health; education; school starting age; children